(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The objective of this paper is to investigate the Material removal rate of 10% of pista shell powder reinforced epoxycomposite compared to plain epoxy resin composite. Materials and Methods: Experiment was carried out for two groups namely Group 1 (Plain Epoxy Resin composites) and Group 2 (10% of pista shell powder reinforced epoxy composite). The sample size calculation was done using a G power calculated and pre-test power is 80% mean value and standard deviation are 0.5 and 0.1 for without filler and 0.2 and 0.06 for filler respectively and 16 samples per group were taken for study. Pista shell powder contains heavy calcium carbonate. Statistical analysis was performed using the SPSS software tool.G power is taken as 80%. Results: It was inferred from the results that the material removal rate of the plain epoxy resin composite was 0.510 mm3/min and 10% of pista shell powder reinforced epoxy composite was 0.798 mm3/min. The significance value obtained from statistical value analysis p=0.00; p<0.05 and hence no significant variation observed between the groups. Conclusion: Within the limitations of the study,it is found that the Material removal rate of novel 10% of pista shell powder reinforced Novel polymer composite was better than the plain epoxy resin composite by approximately 30%.